Cooperative Control Strategy for Power Quality Based on Heterogeneous Inverter Parallel System - Qing Wang; Hongzhao Zhang; Fan Xiao; Yuting Zheng; Qi Guo (Energies)
Multi-functional grid-connected inverters (MFGCIs) have attracted much attention for their auxiliary services to improve power quality in microgrids and new energy generation systems. However, power quality enhancement based on MFGCIs often only considers a single control method. The regulation potential of multiple control-type inverters is not fully utilized. To suppress harmonic and support voltage, a cooperative control strategy based on the parallel system of a grid-following (GFL) inverter and a grid-forming (GFM) inverter is proposed. The topology of the MFGCIs is introduced and a mathematics model is deduced. Secondly, a specific-order harmonic compensation method is proposed for the harmonic suppression at the point of common coupling (PCC). The harmonic current is realized to be shared according to the inverter capacity. The reactive power output of the heterogeneous inverters is coordinated by calculating the reactive power compensation and reactive power allocation so that the PCC voltage always stays near the rated voltage. Finally, the effectiveness of the proposed control strategy is verified by simulation and experiment.